ChemInform Abstract: Resorcinarene‐Based Cavitands as Building Blocks for Crystal Engineering. Issue 52 (6th December 2016) - Pinalli, R.; Dalcanale, E.; Ugozzoli, F.; Massera, C.
Abstract: Review: "classic" and recent results concerning their chemistry, applications and crysal structure; 128 refs.